s.s
 👍
 👎
 👁

 👍
 👎
👤Writeacher
Respond to this Question
Similar Questions

calculus
h(t)=cot t a.) [pi/4,3pi/4] b.) [pi/6,pi/2] Find the average rate of change of the function over the give n interval and intervals. Please show step by step instructions. Thanks

Algebra
Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A step 4 B step 1 C step 2 D

math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

Math
April rewrote a quadratic function in vertex form. h(x)=5^230x+30 step 1 h(x)=5(x^26x+ )+30 step 2 h(x)=5(x^26x+9)+3045 step 3 h(x)= 5(x3)^2+15 In which step did they make a mistake? and how? Please help

Calculus
Use the fourstep process to find the slope of the tangent line to the graph of the given function at any point. f(x) = 16  10 x Step 2: f(x + h)  f(x) = Step 4: f'(x) = lim(h>0)(f(x + h) f(x))/h =

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

CHEM
The decomposition of nitrogen dioxide 2NO2>2NO+O2 occurs in a twostep sequence at elevated tempatures. the first step lis NO2> NO+O. predict a possible second step that, when combined with the first step, gives the complete

math
Omar wanted to know if x−5 is a factor of the polynomial p(x)=x3−6x2−x+30. He applied the Factor Theorem and concluded that x−5 is a factor of p(x), as shown in the following work. Step 1: p(5)=53−6(52)−5+30 Step 2:

Math (Check 2 answers please)
1. What is the value of b in the equation b + 8 = 13? A. 5**** B. 8 C. 13 D. 21 2. The steps below show the incomplete solution to find the value of x for the equation 7x − 3x − 4 = −1 + 21: Step 1: 7x − 3x − 4 = −1 +

math
10a) Simplify the expression and explain each step. 12 + 3(2y – 3) Step 1: apply distributive property Step 2: combine like terms Step 3: simplify b) Factor the expression completely. 18b – 12 What is the GCF of 18 and 12? Use
You can view more similar questions or ask a new question.